Care in the hospital routine: perspectives of professional managers and nursing assistants - Josane Rosenilda da Costa; Sonia Silva Marcon; Elen Ferraz Testón; Guilherme de Oliveira Arruda; Hellen Emília Peruzzo; Hellen Pollyanna Mantello Cecilio; Verônica Francisquete Marquete (Universidade Federal do Ceará, 2020)
Objective: to understand the meanings of care in the hospital routine for nursing professionals working in management and care. Methods: qualitative study that adopted the Human Care Theory as a reference. 38 nursing professionals participated, including service coordinators, directors, nurse assistants and nursing technicians. Data collection took place through semi-structured interviews recorded, transcribed and submitted to Content Analysis, Thematic modality. Results: three categories emerged: possible and necessary: the rescue of meaning and subjective values of care; scientific and human potential as a determinant of care; and difficulties involved in care. Conclusion: care in the hospital routine was perceived by nursing managers and care professionals as an event monitored and influenced by operational aspects, of a more objective nature, as institutional barriers for bonding, but mainly due to subjective aspects, linked to the way of being of the heath professional which shape humanistic care.